A Bibliometric Mapping and Research Gap Analysis of Greenwashing Studies in Scopus (2012–2025) - Listyorini, Inon; Sutopo, Bambang (Faculty of Islamic Economics and Business, State Islamic University Sunan Kalijaga, 2025)
Purpose: This paper aims to formulate research opportunities on greenwashing. It is motivated by the growing prominence of environmental issues in accounting research and the emergence of greenwashing practices, which create the impression that a company’s environmental performance is strong without requiring substantial financial investment. Method: This study employs bibliometric analysis based on 138 articles published between 2012 and 2025, sourced from the Scopus database. Frequency analysis was conducted using Microsoft Excel, with the results visualized through VOS viewer and Harzing’s Publish or Perish citation matrix. Findings: There are research opportunities on greenwashing in relation to ESG, reporting assurance, SDG washing, CSR decoupling, the circular economy, bank financing, stock price crash risk, sustainable investment, social media, green bonds, transparency, institutional investors, corporate reputation, and environmental disclosure. Novelty: There are research opportunities on greenwashing in relation to ESG, reporting assurance, SDG washing, CSR decoupling, the circular economy, bank financing, stock price crash risk, sustainable investment, social media, green bonds, transparency, institutional investors, corporate reputation, and environmental disclosure.